Thermolysis of biphenylene toward cyclo-ortho-phenylenes [data] - Ehjeij, Daniel; Rominger, Frank; Bunz, Uwe H. F.; Freudenberg, Jan; Müllen, Klaus (Universität, 2024)
The solvent and catalyst free thermolysis of biphenylenes at 350 °C furnishes [n]cyclo-ortho-phenylenes ([n]COPs, n=4–10) in one step and in high yields. At 400 °C biphenylene dimerizes into tetraphenylene, but lower reaction temperatures produce cyclooligomers. If suitably substituted, the oligomers are soluble and can be isolated and characterized. The products are exclusively cyclic. In the crystalline state, [6]COP displays an alternating crown-shaped conformation. (2023-12-12)
Gesehen am 13.05.2024
Keywords: Forschungsdaten; Datenbank